Controller Optimization Evaporation Process of Salt Solution in Green House using Fuzzy Logic Controller - Faikul Umam; Hairil Budiarto; Sri Wahyuni (Universitas Trunojoyo Madura, 2019)
Salt processing commonly conducted by using heat energy from solar. Process begins with heating salt water from sea on the embankment with a period approximately 30 to 40 days. In the rainy season the quantity of salt produced decreases due to weather. Some salt farmers prefer not to produce in the rainy season because it's a high risk percentage. The aim from this research is to help them, we create greenhouse technology that can optimize the process of evaporation of old salt water into salt. This technology allows salt farmers to produce salt without regard to the influence of the weather, both dry and rainy seasons. This technology maintains indoor temperatures according to the best temperature of the evaporation process using heating elements. Technology in the form of a greenhouse with a prism-shaped roof. If the temperature in the room exceeds the optimal temperature, then the heat in the room will be released through the exhaust air until the temperature becomes optimal again. This system uses the Fuzzy Logic Control method to regulate temperature, humidity and air pressure